Developing Students’ Writing Competency of News Item Text through Online English News - Taufik Afdal; Joko Iswanto; Fety Surfaifel (ELT in Focus, 2022)
This research seeks to investigate the application of online English news in teaching the writing of news item texts. An experimental study with quantitative data analysis was employed in the present study. The instruments used were tests (pre-test, post-test), and a questionnaire consisting of 10 questions. The researcher administered a pre-test in the first place before applying online news. Then, at the end of the course, the researcher administered a post-test to find out the final results of the application. The population in this study was students of class XII with a sample of 54 students. To assess students’ writing score, an analytic scoring rubric developed by Jacob et al was adopted. In this study, it can be seen from the results of the pre-test and post-test which were calculated using an independent sample T-test through the SPSS program, that the significance obtained was 0.01, which means that the use of online news texts was used effectively. In the results of the questionnaire, the answers (yes) were chosen as many as 113; the answers (sometimes) were chosen as many as 92; and the answers (no) were 65. This means that majority of students at MAN Tanjung Pinang responded positively towards the application of online English news.